VD_FINDINFO HC / 2014 / 940 vom 12. November 2014 - VD Tribunal cantonal (2014)
PREUVE À FUTUR, EXPERTISE, AVANCE DE FRAIS, DÉPENS | 367 al. 2 CO, 102 CPC (CH), 107 al. 1 let. f CPC (CH), 110 CPC (CH), 158 al. 1 CPC (CH)